Multiple targets detection in the marine environment using matlab - SK, Jainuddin; P, Satyanarayana; V.B.K.L, Aruna (International Journal of Engineering and Technology, 2018)
This paper implements multiple targets detection against sea clutter by mathematically modeling target as a single point target and sea-clutter as k-distribution model and observing the deterioration in the effective operation of radar using signal processing by matlab. A Variability Index (VI) algorithm is suggested for detection on the basis of constant false-alarm rate (CFAR) property even in heteroge-neous conditions. Comparative analysis of VI-CFAR against various CFAR methods (CA, GO, SO, OS) for multiple targets detection in heterogeneous environment is done in this paper. Comparison and evaluation is done by means of the data which is simulated in MATLAB. The logical operation of the method is verified in heterogeneous condition.Â